Capacidade de adsorção da atrazina em biocarvões produzidos a partir de diferentes espécies de bambus - Sbizzaro, Mariana (2020)
Biochar is a solid carbonaceous compound, derived from the pyrolysis of several biomasses, with several benefits and applicability. Among them, pesticide adsorption has been highlighted due to factors such as low costs and easiness to produce biochar and to apply the adsorption technique. In addition, it comes out as an alternative to residues destination and socioenvironmental contribution to immobilize pesticides, since studies have reported many adverse effects of pesticides on the environment as well as on human and animal health. Atrazine is widely used in several countries and has a great tendency to contaminate mainly waters, due to its characteristics of mobility and persistence. Thus, the first experiment on a laboratory scale was conducted with the purpose of studying the capacity of six different bamboo biochars, produced at different pyrolysis temperatures to adsorb atrazine using classical modeling. Biochars were produced from the following bamboo species: Guadua sp., Chusquea aff. gracilis, Merostachys skvortzovii and Apoclada simplex at 350, 450 and 550 ºC temperatures, for bamboo of the species Guadua sp. and at 500 ºC for bamboos of the species Chusquea aff. gracilis, Merostachys skvortzovii and Apoclada simplex, totaling six biochars, named as BN350, BN450, BN550, BB500, BT500 and BF500. Physical-chemical, textural and morphological characterizations were carried out on the six biochars. Biochars showed a carbon percentage higher than 65%, specific surface area (SSA) ranging from 2.22 - 25.5 m2 g -1 , pore diameter from 31.23 - 40.77 Å, and the lowest values of pore volume and micropore volume were observed for BN350. The analysis of Fourier Transform Infrared Spectroscopy (FTIR) of biochars has recorded the presence of functional groups related to materials. And, Scanning Electron Microscopy (SEM) micrographs showed some great porosity of biochars. Besides, kinetic and equilibrium isotherm experiments were carried out in batch systems, with triplicate analyses and one control. Kinetic data of atrazine adsorption were obtained at the initial solution concentration (4 mg L -1), and kinetic equilibrium time was of 12 days. The equilibrium atrazine adsorption capacities were 1.4 (BN350), 2.0 (BN450), 1.5 (BN550), 1.5 (BB500), 1.5 (BT500) and 1.2 mg g –1 (BF500). The kinetic models of pseudo-first order and pseudo-second order were also evaluated, in which the pseudo-second order model adjusted most adequately to most of the data of the evaluated biochars. However, it is suggested as an ongoing study the evaluation of models that explain adsorptive mechanism of biochars bamboo-atrazine system. Equilibrium isotherm models of Langmuir and Freundlich were evaluated, in which, the BT500 data were better represented by the Langmuir model, while the Freundlich model adjusted more adequately to the BN550 data. However, it is recommended for other biochars to evaluate other models of isotherms and statistical parameters that may be more conclusive. In the second trial, the adsorption capacity of atrazine in the six bamboo biochars was evaluated using phenomenological modeling. Langmuir, BET (Brunauer-Emmett-Teller) and Freundlich equilibrium isotherm models were evaluated. The adsorption equilibrium data showed that Langmuir isotherm described adequately the investigated systems for the six biochars, providing evidence to the evidence presented in the first study. The kinetic mechanism was evaluated using three models of mass transfer, diffusion in film, adsorption on surface and intraparticle diffusion (method Homogeneous Surface Diffusion Model - HSDM). According to the description of adsorption kinetics, the intraparticle diffusion model adjusted itself well to the data of the six biochars, and provided values of intraparticle diffusion coefficient (Def) at 10-8 to 10-9 cm² min-1 magnitude.